A simplified hysteresis current control for cascaded converter fed switched reluctance motor - Anuradha Devi Tellapati; Malligunta Kiran Kumar (International Journal of Electrical and Computer Engineering (IJECE), 2019)
Simple constructional features with no windings on rotor circuit and robustness make switched reluctance motor (SRM) a most used motors in industrial applications. Peak motor voltage rating depends on the rated voltage of the power switches. In conventional asymmetrical converter driving SRM, voltage rating of the motor depends on rating of power electronic switches in converter. Demand to rise the motor rating insists to put pressure on converter switching components which results in increased switching losses. A cascaded converter topology for SRM reduces the rating of switching components as compared to conventional converters for SRM. This paper presents a cascaded converter fed SRM drive with reduced switching losses. The paper presents a simplified hysteresis current control (HCC) for cascaded converter fed SRM. Simplified HCC control method reduces switching losses as HCC is applied to only one bridge of cascaded converter. Though the performance of the SRM remains same with cascaded converter fed SRM with HCC applied to only one bridge or to two bridges and with conventional asymmetrical converter, the switching losses are reduced to a great extent when HCC applied to one bridge of cascaded converter fed SRM. Performance of SRM is illustrated with conventional asymmetrical converter fed SRM and is compared to cascaded converter while HCC applied to only one bridge and applied to two bridges of cascaded converter. Proposed work is simulated using MATLAB/SIMULINK and results are presented.